Epidemiology of nontuberculous mycobacterial pulmonary disease in Europe and Japan by Delphi estimation. (November 2020) - Schildkraut, Jodie A.; Gallagher, Jack; Morimoto, Kozo; Lange, Christoph; Haworth, Charles; Floto, R. Andres; Hoefsloot, Wouter; Griffith, David E.; Wagner, Dirk; Ingen, Jakko van
Abstract: Background: Nontuberculous mycobacterial pulmonary disease (NTM-PD) is an emerging opportunistic infection, but basic epidemiological data are lacking in most regions. We have investigated epidemiology and diagnostic and treatment practices in five EU countries (United Kingdom, Spain, Italy, France, Germany; EU5) and Japan. Study design: and methods : Annual prevalence in each country was established using a 2-round Delphi method in combination with a regional prevalence-estimation model that incorporated data obtained from a blinded physician screening survey (3154 physicians) and a real-world NTM-PD treating-physician/patient-chart observational study (619 physicians – 1429 patient charts). Results: The annual prevalence of NTM-PD was estimated at 6.2/100, 000 in the EU5 and 24.9/100, 000 in Japan. Overall prevalence between the EU5 was comparable, while differences in regional prevalence were found to be pronounced in France and The United Kingdom. Regional differences were also found in Japan, with the majority of cases in Chubu and Kanto regions. Conclusion: This new methodology for obtaining often missing regional-level epidemiological data reveals dramatic variations in NTM-PD annual prevalence and helps pinpoint areas that may merit special preventative and treatment focus. Highlights: NTM-PD prevalence is 6.2/100, 000 and 24.9/100, 000 for EU5 and Japan, respectively. A large regional heterogeneity regarding NTM-PD prevalence is seen within countries. A greater clinical awareness regarding proper diagnosis and treatment of NTM-PD is necessary.